Model Perubahan Warna Keripik Buah selama Penggorengan Vakum - Jamaluddin Jamaluddin; Budi Rahardjo; Pudji Hastuti; Rochmadi Rochmadi (agriTECH, 2011)
The natural colour of fruit flaky product is one of specific property prefered by consumer. To maintain the natural colourof the fruit flaky during frying, it is necessary to pay attention the characteristic changes of raw material and control the process in order not to have much changes to get the intended colour. The objective of this research is to develop empirically mathematical model of fruit flaky colour changes during vacuum frying process by considering the change of water and sucrose contents in the product. Sample of the research were jack fruits fried in the temperature of 70–100OC, frying duration of 15–60 minutes, and vacuum pressure of 13-23 kPa. The observed parameters are colour (L), colour (a), colour (b), water and sukrose contents before and after frying. The result showed that colour changes (L, a and b) were influenced by free water vaporization and sukrose decreasing in product, so empirically, the developed mathematical model of colour changes (L, a and b) can be used to predict fruit flaky colour changes during vacuum frying.ABSTRAKWarna alami pada produk keripik buah adalah merupakan salah satu sifat khas yang disukai oleh konsumen, untukmempertahankan warna alami keripik buah agar tidak banyak mengalami perubahan selama dalam penggorengan, perlu diperhatikan perubahan karakteristik bahan baku dan pengendalian proses, agar warna keripik buah yang dihasilkan sesuai dengan yang diinginkan. Penelitian ini bertujuan untuk mengembangkan secara empirik model matematik perubahan warna keripik buah selama dalam proses penggorengan vakum dengan mempertimbangkan ke dalam model perubahan kadar air dan kadar sukrosa di dalam padatan. Sampel penelitian adalah buah nangka digoreng pada suhu70-100 OC, lama penggorengan 15-60 menit dan tekanan vakum 13-23 kPa. Parameter yang diamati adalah warna (L), warna (a), warna (b), kadar air dan kadar sukrosa sebelum dan setelah sampel digoreng. Hasil penelitian menunjukkan perubahan warna L, a dan b dipengaruhi oleh penguapan air bebas dan penurunan kadar sukrosa di dalam padatan, sehingga secara empirik model matematik perubahan warna L, a dan b yang dikembangkan dapat digunakan dengan baik untuk memprediksi perubahan warna keripik buah selama dalam proses penggorengan secara vakum.